Gut-to-brain spreading of pathology in synucleinopathies: A focus on molecular signalling mediators - Schmitt, Verena; Masanetz, Rebecca Katharina; Weidenfeller, Martin; Ebbinghaus, Lara Savannah; Süß, Patrick; Rosshart, Stephan Patrick; von Hörsten, Stephan; Zunke, Friederike; Winkler, Jürgen; Xiang, Wei (Behavioural Brain Research, 2023)
Synucleinopathies are a group of neurodegenerative disorders, classically characterized by the accumulation of aggregated alpha synuclein (aSyn) in the central nervous system. Parkinson's disease (PD) and multiple system atrophy (MSA) are the two prominent members of this family. Current treatment options mainly focus on the motor symptoms of these diseases. However, non-motor symptoms, including gastrointestinal (GI) symptoms, have recently gained particular attention, as they are frequently associated with synucleinopathies and often arise before motor symptoms. The gut-origin hypothesis has been proposed based on evidence of an ascending spreading pattern of aggregated aSyn from the gut to the brain, as well as the comorbidity of inflammatory bowel disease and synucleinopathies. Recent advances have shed light on the mechanisms underlying the progression of synucleinopathies along the gut-brain axis. Given the rapidly expanding pace of research in the field, this review presents a summary of the latest findings on the gut-to-brain spreading of pathology and potential pathology-reinforcing mediators in synucleinopathies. Here, we focus on 1) gut-to-brain communication pathways, including neuronal pathways and blood circulation, and 2) potential molecular signalling mediators, including bacterial amyloid proteins, microbiota dysbiosis-induced alterations in gut metabolites, as well as host-derived effectors, including gut-derived peptides and hormones. We highlight the clinical relevance and implications of these molecular mediators and their possible mechanisms in synucleinopathies. Moreover, we discuss their potential as diagnostic markers in distinguishing the subtypes of synucleinopathies and other neurodegenerative diseases, as well as for developing novel individualized therapeutic options for synucleinopathies.
CRIS-Team Scopus Importer:2023-08-25
Keywords: Alpha synuclein; Gut-to-brain communication; Inflammatory bowel disease; Multiple system atrophy; Parkinson's disease